Quantification of regional left ventricular function in Q wave and non-Q wave dysfunctional regions by tissue Doppler imaging in patients with ischaemic cardiomyopathy. Issue 11 (31st October 2003) - Bountioukos, M; Schinkel, A F L; Bax, J J; Rizzello, V; Rambaldi, R; Vourvouri, E C; Roelandt, J R T C; Poldermans, D
Abstract : Objective: To quantify regional left ventricular (LV) function and contractile reserve in Q wave and non-Q wave regions in patients with previous myocardial infarction. Design: An observational study. Setting: Tertiary care centre. Patients: 81 patients with previous myocardial infarction and depressed LV function. Interventions: All patients underwent surface ECG at rest and pulsed wave tissue Doppler imaging at rest and during low dose dobutamine infusion. The left ventricle was divided into four major regions (anterior, inferoposterior, septal, and lateral). Severely hypokinetic, akinetic, and dyskinetic regions on two dimensional echocardiography at rest were considered dysfunctional. Main outcome measures: Regional myocardial systolic velocity (Vs) at rest and the change in Vs during low dose dobutamine infusion (ΔVs) in dysfunctional regions with and without Q waves on surface ECG. Results: 220 (69%) regions were dysfunctional; 60 of these regions corresponded to Q waves and 160 were not related to Q waves. Vs and ΔVs were lower in dysfunctional than in non-dysfunctional regions (mean (SD) Vs 6.2 (1.9) cm/s v 7.1 (1.7) cm/s (p < 0.001), and ΔVs 1.9 (1.9) cm/s v 2.6 (2.5) cm/s (p = 0.009), respectively). There were no significant differences in Vs and ΔVs among dysfunctional regions with and without Q waves (Q wave regions: Vs 6.2 (1.8) cm/s, ΔVs 1.6 (2.2) cm/s; non-Q wave regions: Vs 6.3 (1.9) cm/s, ΔVs 2.0 (2.0) cm/s). Conclusions: Quantitative pulsed wave tissue Doppler demonstrated that, among dysfunctional regions, Q waves on the ECG do not indicate more severe dysfunction, and myocardial contractile reserve is comparable in Q wave and non-Q wave dysfunctional myocardium.